High resolution visualization of the redox activity of Li2O2 in non-aqueous media: conformal layer vs. toroid structure12. Issue 24 (7th March 2018) - E, Sharel P.; Kang, Minkyung; Wilson, Paul; Meng, Lingcong; Perry, David; Basile, Andrew; Unwin, Patrick R.
Abstract : A strong relationship between the surface structure and the redox activity of Li2 O2 is visualized directly using scanning electrochemical cell microscopy, employing a dual-barrel nanopipette containing a unique gel polymer electrolyte. Abstract : A strong relationship between the surface structure and the redox activity of Li2 O2 is visualized directly using scanning electrochemical cell microscopy, employing a dual-barrel nanopipette containing a unique gel polymer electrolyte. These measurements reveal considerable local heterogeneity with significantly enhanced electrochemical activity at toroidal Li2 O2 structures when compared to the conformal layer that is usually formed on the cathode of Li–O2 batteries.